2018
DOI: 10.1589/jpts.30.1359
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the relationship between foot skin temperature and blood flow in type 2 diabetes mellitus patients: a cross-sectional study

Abstract: [Purpose] The current study aimed to investigate the reliability of infrared thermography as a method of determining foot skin temperature, and to determine the relationship between foot skin temperature and blood flow in type 2 diabetes mellitus (DM) patients. [Participants and Methods] Eighty-five patients were recruited and their foot skin temperature and the ankle brachial index (ABI) were measured using infrared thermography and an automated oscillometry, respectively. A correlation between foot skin temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The increase in plantar temperatures in group 3 (diabetics with PN) with respect to control was found to be similar to some studies [16][17][18].Explanation about increased temperature is due to peripheral neurological dysfunction caused by permanent vasodilatation produced by vasoconstriction deficiency of autonomic motor response [19].…”
Section: Discussionsupporting
confidence: 85%
“…The increase in plantar temperatures in group 3 (diabetics with PN) with respect to control was found to be similar to some studies [16][17][18].Explanation about increased temperature is due to peripheral neurological dysfunction caused by permanent vasodilatation produced by vasoconstriction deficiency of autonomic motor response [19].…”
Section: Discussionsupporting
confidence: 85%
“…Except for the sacrum after 2 hours, there was a nearly perfect reliability for skin temperature measurements, which is also supported by previous research 29 . Using different infrared thermal imaging systems Liu et al reported an ICC of 0.82 for back skin 37 and Chatchawan et al reported ICCs for foot skin temperatures higher than 0.9 38 . This indicates that skin temperature measurements using infrared methods are reliable.…”
Section: Discussionsupporting
confidence: 76%
“… 29 Using different infrared thermal imaging systems Liu et al reported an ICC of 0.82 for back skin 37 and Chatchawan et al reported ICCs for foot skin temperatures higher than 0.9. 38 This indicates that skin temperature measurements using infrared methods are reliable. Limits of agreement and the SEM also indicate small absolute measurement errors not exceeding 1°C.…”
Section: Discussionmentioning
confidence: 95%
“…Blood flow mechanics have also been proposed to play a role in skin thermoregulation ( Chatchawan et al, 2018 ; Walloe, 2016 ). The foot is primarily innervated by the posterior tibial artery which transverses the medial foot arch area ( Sun, Jao & Cheng, 2005 ).…”
Section: Discussionmentioning
confidence: 99%